Should Spotify bring voice assist technology to the smart speaker market? - Diller, Christopher; Pursley, Stewart; Gentry, Richard (London : SAGE Publications: SAGE Business Cases Originals, 2022)
In 2018, Spotify started selling its shares publicly on the New York Stock Exchange. The Swedish-based start-up that launched in 2008 was on its way to becoming the largest music streaming platform in the world. At the time it was going public, Spotify was used in 61 countries, had 159 million active users, and hosted a music library of 35 million songs.Over the last decade, Spotify has focused on increasing its music library available to stream and differentiating its brand from competitors by adding music videos, live clips, and podcasts to its service. It has created a series of personalized playlists based on users' preferences and song history. It has also begun hosting live events. All of these offerings have added to its popularity and brand loyalty from its streamers.However, one segment that Spotify has not tapped into (an area that its competitors already dominate) is the voice assist speaker system market. Reports have shown that Spotify is looking to add voice assist capabilities to its platform, and in turn, considering the development of a proprietary smart speaker device.By 2017, the voice assist speaker market had become a global phenomenon valued at USD 4.4 billion and is projected to reach USD 23.3 billion by 2025. Spotify has been focused on maintaining its lead in music streaming, but now, smart speaker manufacturing companies will be able to disintermediate Spotify as a non-essential application, breaking its connection to customers. But with the current success of Spotify's music streaming platform and its competitors focused on the smart speaker segment that Spotify has no control over, Spotify must decide whether or not to follow the first movers and enter the voice assist speaker market.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Streaming technology (Telecommunications) -- Decision making